2020
DOI: 10.1097/hjh.0000000000002592
|View full text |Cite
|
Sign up to set email alerts
|

Differences in patient and physician perspectives on pharmaceutical therapy and renal denervation for the management of hypertension

Abstract: Objective: To study patient and physician attitudes to pharmaceutical therapy and renal denervation for the management of hypertension. Methods: Data were analyzed from 19 market research studies in Western Europe and the United States conducted between 2010 and 2019 to obtain quantitative and qualitative perspectives. The analysis incorporated insights from 2768 patients and the experiences of 1902 physicians either actively performing or interested to perform device proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 27 publications
2
26
3
Order By: Relevance
“…In this study, patient reported burden of disease rankings are developed and compared with the usual expert reported burden of disease rankings. Prior research shows that patient reported and expert reported burden of disease could differ as patients tend to focus on subjective health experiences (quality of life) and experts tend to focus on mortality and disability (quantity of life) 8 10 . In accordance, this study shows that these differences are also reflected in the often used burden of disease rankings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, patient reported burden of disease rankings are developed and compared with the usual expert reported burden of disease rankings. Prior research shows that patient reported and expert reported burden of disease could differ as patients tend to focus on subjective health experiences (quality of life) and experts tend to focus on mortality and disability (quantity of life) 8 10 . In accordance, this study shows that these differences are also reflected in the often used burden of disease rankings.…”
Section: Discussionmentioning
confidence: 99%
“…Although these rankings provide valuable insight in the biomedical burden of different diseases, they do not yet provide insight in the psychological burden of different diseases experienced and reported by patients on a daily basis. Since patient reported burden of disease often differs from expert reported burden of disease, deviations between patient reported and expert reported burden of disease rankings are likely to occur 8 10 . In order to understand how these rankings differ, it is important to develop patient reported burden of disease rankings and discuss how these compare with the usual expert reported burden of disease rankings.…”
Section: Introductionmentioning
confidence: 99%
“…72 In a recent survey, patient and physician attitudes toward pharmaceutical therapies and RDN for hypertension may be differ relative to severity of hypertension and medication burden. 73 Specifically, preference for device-based therapy among patients may be highest among those not taking medications and may be independent of BP severity. HARC encourages incorporating such assessments in device-based hypertension trials and developing health status models specific to this area of study.…”
Section: Patient-related Outcomes and Preferencementioning
confidence: 99%
“…Patients’ regard for RDN often differs from their physicians’ perspective. This preference for RDN need not necessarily happen only for those with high pill burden or very severe hypertension [ 21 23 ].…”
Section: Patient Preferencementioning
confidence: 99%